Dovitinib enhances temozolomide efficacy in glioblastoma cells. Issue 8 (5th June 2017) - Thanasupawat, Thatchawan; Natarajan, Suchitra; Rommel, Amy; Glogowska, Aleksandra; Bergen, Hugo; Krcek, Jerry; Pitz, Marshall; Beiko, Jason; Krawitz, Sherry; Verma, Inder M.; Ghavami, Saeid; Klonisch, Thomas; et al.
Abstract : The multikinase inhibitor and FDA‐approved drug dovitinib (Dov) crosses the blood–brain barrier and was recently used as single drug application in clinical trials for GB patients with recurrent disease. The Dov‐mediated molecular mechanisms in GB cells are unknown. We used GB patient cells and cell lines to show that Dov downregulated the stem cell protein Lin28 and its target high‐mobility group protein A2 (HMGA2). The Dov‐induced reduction in pSTAT3 Tyr705 phosphorylation demonstrated that Dov negatively affects the STAT3/LIN28/Let‐7/HMGA2 regulatory axis in GB cells. Consistent with the known function of LIN28 and HMGA2 in GB self‐renewal, Dov reduced GB tumor sphere formation. Dov treatment also caused the downregulation of key base excision repair factors and O 6 ‐methylguanine‐DNA‐methyltransferase (MGMT), which are known to have important roles in the repair of temozolomide (TMZ)‐induced alkylating DNA damage. Combined Dov/TMZ treatment enhanced TMZ‐induced DNA damage as quantified by nuclear γH2AX foci and comet assays, and increased GB cell apoptosis. Pretreatment of GB cells with Dov ('Dov priming') prior to TMZ treatment reduced GB cell viability independent of p53 status. Sequential treatment involving 'Dov priming' and alternating treatment cycles with TMZ and Dov substantially reduced long‐term GB cell survival in MGMT+ patient GB cells. Our results may have immediate clinical implications to improve TMZ response in patients with LIN28 + /HMGA2 + GB, independent of their MGMT methylation status. Abstract : Dovitinib, a multikinase inhibitor, has recently been used as a monotherapy for the treatment of glioblastoma. Here, we show that dovitinib inhibits the STAT3/LIN28/Let7/HMGA2 regulatory pathway and downregulates HMGA2 in glioblastoma cells, reducing their capacity for self‐renewal. Dovitinib (DOV) increases sensitivity to the DNA‐alkylating agent temozolomide (TMZ) in glioblastoma cells. Dovitinib‐mediated downregulation of the DNA repair proteins MGMT, MPG, APE1, FEN1, XRCC1 and PARP1 increases glioblastoma cell apoptosis upon TMZ‐induced DNA damage.